HOSPITALITY INDUSTRY, A CONTRACT IS AN AGREEMENT OR PROMISE - Ma Junyu (Jurnal Pembaharuan Hukum, 2020)
In hospitality industry, a contract is an agreement or promise made between two or more parties that the courts will enforce. In other words, it is a set of rules governing the relationship, content and validity of an agreement between two or more persons. Normally, it is related to the sale of goods, provision or services or exchange of interests or ownership. A valid contract can be considered as the moment that the offer is accepted. For example, you have been agreed to purchase with someone’s old cupboard for 1200 Yuan, that is mean you have a valid contract. Once you paid to them and they give you the cupboard which means the contract is complete. In general, a valid contract may be established either in writing or verbally. That is mean it can be a verbal form of contract, and it also can be a written form of contract. A verbal contract is any contract which is expressed in words by spoken. While for the written contract, it is a contract generally refers to a written document outlining an agreement. More often than not, it is usually a good idea to have a written contract if a transaction that is worth more than a limit.